2017
DOI: 10.3892/ijmm.2017.3337
|View full text |Cite
|
Sign up to set email alerts
|

Codonopis�bulleynana Forest ex Diels inhibits autophagy and induces apoptosis of colon cancer cells by activating the NF-κB signaling pathway

Abstract: Despite its favorable clinical efficacy, oxaliplatin-based chemotherapy frequently results in treatment withdrawal and induces liver damage in colon cancer. Therefore, it is important to develop novel drugs, which can safely and effectively complement or replace the therapeutic effects of oxaliplatin. Codonopis bulleynana Forest ex Diels (cbFeD) has wide range of pharmacological effects, including anticancer effects. In the present study, the anticancer activity of cbFeD and its potential molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…POS may inactivate NF-κB and affects the level of its downstream genes [cyclin D1 ( 135 ), TNF-α ( 136 ), and IL-6 ( 115 )] have been tested in NF-κB signaling pathway. Some data show that POS are the most potent activators of NF-κB signaling (Figure 6 ) ( 137 ), whereas the activation of NF-κB signaling pathway will promote CC apoptosis ( 138 ).…”
Section: Pos Regulates Nuclear Factor-kappa B (Nf-κb) Pathwaymentioning
confidence: 99%
“…POS may inactivate NF-κB and affects the level of its downstream genes [cyclin D1 ( 135 ), TNF-α ( 136 ), and IL-6 ( 115 )] have been tested in NF-κB signaling pathway. Some data show that POS are the most potent activators of NF-κB signaling (Figure 6 ) ( 137 ), whereas the activation of NF-κB signaling pathway will promote CC apoptosis ( 138 ).…”
Section: Pos Regulates Nuclear Factor-kappa B (Nf-κb) Pathwaymentioning
confidence: 99%
“…Our previous studies have confirmed that Notch signaling promoted osteogenic differentiation of MSCs induced by BMPs (BMP2, 4, 6, 7, and 9) through BMP signaling pathway 22 – 24 . Mitogen-activated protein kinases (MAPKs) are key branch of non-Smad BMP pathway.…”
Section: Resultsmentioning
confidence: 61%
“…Since BMPs and Notch signaling pathway play an important role in osteogenic differentiation, and our previous studies have confirmed that BMP9 had a strong stimulative ability 43 , whereas Notch signaling alone exerted no effect but could significantly promote BMP9-induced osteogenic differentiation 24 during this process, we hypothesized that CCN3 plays an inhibitory role by affecting BMP9 and Notch signaling pathway. We first examined the effect of CCN3 on BMP9 expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, many studies have investigated the autophagic pathways in order to develop new potential targeted therapies [7][8][9][10][11]. In addition, autophagic drugs tend to induce cell autophagic death (type II cell death) and cause colon cancer cell death [12][13][14][15]. For instance, in the phase 1/2 clinical trials, NVP-BEZ235 was observed to induce colon cancer cell apoptosis and autophagy simultaneously [16,17].…”
Section: Introductionmentioning
confidence: 99%